Peningkatan Pengetahuan dan Keterampilan Guru Sekolah Dasar dalam Mengurangi Pencemaran Sampah Plastik Melalui Pelatihan Pembuatan KOKEDAMA - Eddy Noviana; Otang Kurniaman; Zufriady Zufriady; Guslinda Guslinda; Erlisnawati Erlisnawati; Munjiatun Munjiatun; Muhammad Ramadhan; Lilis Mistina; Ria Novianti (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2021)
This training activity aims to provide teachers with knowledge and skills in making kokodema an environmentally friendly medium in reducing plastic waste pollution in schools. The activities carried out consist of three activity activities, namely pre-activity, implementation of activities, and post-activity. Pre-activity activities are initial exploratory activities to find reasons for teachers/activity participants to participate in activities. While the implementation of the activity has carried out by providing a list of questions to the teacher/participant, which contained the teacher's initial knowledge of kokedama as an environmentally friendly medium, then continued with the delivery of material. The third activity is post-activity, an activity to process data obtained from participant/teacher responses before and after the activity has carried out. Training activities for making kokodema an environmentally friendly medium can increase the knowledge and skills of teachers in reducing plastic waste pollution in schools. This has shown by the active participation of the participants in participating in training activities ranging from delivering material, taking an active role in discussions, carrying out kokedama making practices and participating actively in evaluation and reflection activities.